The Effect of The Montessori Method Using Large Movable Alphabet Media in Improving Beginning Reading Skills of Grade 1 Students at State Elementary School - Vinah Lusianah; Widia Nur Jannah; Erna Labudasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to determine the effect of the Montessori method, using the Large Movable Alphabet (LMA), on improving the beginning reading skills of first-grade students. A quantitative approach with a one-group pretest-posttest pre-experimental design was employed. The subjects were 20 first-grade students at State Elementary School 1 Pasuruan in the even semester of the 2024/2025 academic year, selected via saturated sampling. The intervention was implemented for four weeks through Montessori-based learning sessions using the LMA. Results showed a significant increase in the mean score from 57.75 (SD = 8.12) in the pretest to 83.25 (SD = 6.47) in the posttest. A paired-samples t-test confirmed a statistically significant difference (t(19) = -12.47, p < .001). The effect size was very large (Cohen's d = 2.79), and the N-Gain score was 0.586 (58.6%), categorized as moderate. This indicates that the Montessori method using the LMA effectively improved students' beginning reading skills. The practical implication is that this method can be an alternative, motivating strategy for early reading instruction in elementary schools, actively engaging students through multisensory media. Recommendations for future research include testing the method with a larger sample, a control group, and over a longer duration.